2013
DOI: 10.1111/ene.12232
|View full text |Cite
|
Sign up to set email alerts
|

Serum brain‐derived neurotrophic factor levels in epilepsy

Abstract: It seems that the concentration of BDNF in serum is associated with disease severity in people with epilepsy and may be a helpful marker for severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
2
34
3
1
Order By: Relevance
“…38 However, the different adult age group of their patients with mature women and a high estrogen level may explain the difference. We found a highly significant difference in the levels of serum and breastmilk BDNF in relation to duration of illness and frequency of seizures per month; this agrees with Hong et al, 30 who found significant negative correlations between seizure frequency and disease duration with serum BDNF levels. One of the objectives of our research was to assess the BDNF value as a marker of epilepsy severity, and we found significant differences in serum and breastmilk BDNF levels for epileptic infants with different disease severity, as the levels were significantly higher in the severe form than in the mild and moderate forms with a p < 0.0001.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…38 However, the different adult age group of their patients with mature women and a high estrogen level may explain the difference. We found a highly significant difference in the levels of serum and breastmilk BDNF in relation to duration of illness and frequency of seizures per month; this agrees with Hong et al, 30 who found significant negative correlations between seizure frequency and disease duration with serum BDNF levels. One of the objectives of our research was to assess the BDNF value as a marker of epilepsy severity, and we found significant differences in serum and breastmilk BDNF levels for epileptic infants with different disease severity, as the levels were significantly higher in the severe form than in the mild and moderate forms with a p < 0.0001.…”
Section: Discussionsupporting
confidence: 92%
“…One of the objectives of our research was to assess the BDNF value as a marker of epilepsy severity, and we found significant differences in serum and breastmilk BDNF levels for epileptic infants with different disease severity, as the levels were significantly higher in the severe form than in the mild and moderate forms with a p < 0.0001. So, serum and milk BDNF levels for epileptic infants are associated with disease severity and may be used as a helpful marker of severity, and this agrees with the results obtained by Hong et al 30 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CREB does not only influence transcription in the nucleus, but also leads to cell wide supply of protein and mRNA that can localize to the synapse when the synapse has been tagged, thereby permitting LTP [88, 89]. One transcript targeted by CREB is the brain derived neurotrophic factor (BDNF) [92], which has been associated to temporal lobe epilepsy in many cases [93] and may serve as a serum marker for epilepsy [94]. …”
Section: Crebmentioning
confidence: 99%
“…Recently, it has been found that decreased plasma BDNF level in adults is reduced with epileptic seizures [14], while serum BDNF concentration in children with epilepsy has not been previously well described. Connolly et al [15] recorded no differences in serum BDNF concentrations between epileptic children and controls.…”
Section: Discussionmentioning
confidence: 99%